The Dynamics of Emotional Intelligence in The Sunnah: An Analytical Study of The Prophet’s (PBUH) Approach to Crisis Management (Lembaga Contrarius Indonesia, 2026)
This research investigates Emotional Intelligence (EI) through the Prophetic methodology, focusing on its application in crisis management. Although EI is a modern psychological framework, its core pillars, specifically self-management and empathy are fundamentally rooted in the life of Prophet Muhammad (PBUH). This study employs a descriptive-analytical approach to examine how the Prophet (PBUH) utilized these emotional competencies to navigate complex social and personal challenges. The study provides specific evidence of the Prophet’s (PBUH) emotional mastery. For instance, his self-management is exemplified in the